A Preliminary Mathematical Analysis for Understanding Transmission Dynamics of Nosocomial Infections in a NICU - Cheong, Taesu; Grant, Jennifer L. (International Journal of Industrial Engineering: Theory, Applications and Practice, 2013)
Nosocomial infections (NIs) have been a major concern in hospitals, especially in high-risk populations. Neonates hospitalized in the intensive care unit (ICU) have a higher risk of acquiring infections during hospitalization than other ICU populations, which often result in prolonged and more severe illness and possibly death. The corresponding economic burden is immense, not only for parents and insurance companies, but also for hospitals faced with increased patient load and resource utilization. In this paper, we attempt to systemically understand the transmission dynamics of NIs in a neonatal intensive care unit (NICU). For this purpose, we present a mathematical model, perform sensitivity analysis to evaluate effective intervention strategies, and discuss numerical findings of the model.